Peran Infrastruktur dan Lembaga Ekonomi Terhadap Implementasi Kebijakan Pembangunan Desa Pesisir (Studi pada Kabupaten Bengkalis): Penelitian - Mukarromah, Aminah; Taryono, Taryono; Afriza, Yunika Nuuru; Ramadani, Oktavia Nada; Despiandra, Aulia; Pusparini, Intan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of infrastructure and economic institutions on the implementation of coastal village development policies in Bengkalis Regency, particularly in achieving the Sustainable Development Goals (SDGs) indicator of Ocean Care Village (SDGs 14). The research employs a quantitative descriptive–verificative approach using secondary data obtained from the Village Development Index (IDM) and Village SDGs 2024 datasets. Data analysis was conducted through Pearson correlation and multiple linear regression tests to examine both partial and simultaneous effects of road quality (X₁) and economic institutions (X₂) on the Ocean Care Village score (Y). The results reveal that neither road quality nor economic institutions have a significant effect, either partially or simultaneously, on the implementation of coastal village development policies, with significance values of 0.742 and 0.403, and an R² value of 0.0088. These findings indicate that other factors, such as community participation, local policy support, and sociocultural capacity, play a more dominant role in policy implementation. The study emphasizes the importance of strengthening governance, enhancing community capacity, and integrating infrastructure development with the blue economy approach to achieve sustainable coastal development in Bengkalis Regency.